Gaya Kepemimpinan Adaptive Leadership Seorang Pemimpin; Studi Literatur - Eka Rachmawati; Ade Rizaldi Hidayatullah; Mochammad Isa Anshori (Jurnal of Management and Social Sciences, 2023)
Adaptive leadership style is very instrumental regarding the problems and challenges that occur, these problems are both from external and internal factors.This study aims to determine the leadership style of Adaptive Leadership of a leader. This research methodology uses qualitative research, and the research method used is the literature study method. The data sources used in this research are books, scientific journals, articles and related documents relevant to the topic of Adaptive Leadership style of a leader. Data Selection Data selection is carried out using certain criteria to determine which sources are relevant and can be used as the basis for analysis in this literature study research. The results showed that the leadership style of Adaptive Leadership has a significant effect on good emotional intelligence, organizational justice, character and plays an important role in career development so as to create a conducive organizational atmosphere.